Effect of Diverse Assessment Methods on Undergraduate Engineering Students’ Performance in Mathematics Courses - Nandini Rai; Yogesh Thakkar; Ravindra Salvi (Journal of Research in Mathematics, Science, and Technology Education, 2026)
Assessment plays a crucial role in shaping how students engage with mathematics in engineering programs. Traditional summative examinations often emphasize rote learning rather than problem-solving or conceptual understanding. This study investigates the impact of diverse assessment methods—including online quizzes, assignments, poster presentations, viva voce, mathematical software applications, note checking, and class participation—on undergraduate engineering students’ performance in mathematics courses. The objectives were to evaluate which assessment strategies most effectively enhance learning outcomes and to provide actionable insights for improving assessment practices in higher education. A quasi-experimental design was employed with a sample of second-year undergraduate engineering students enrolled in core mathematics courses. Data were collected using structured quizzes, software-based tasks, poster presentations, viva assessments, and student surveys, and analyzed using descriptive and inferential statistics. Findings revealed that interactive and technology-driven methods, such as online quizzes and mathematical software tasks, had the strongest positive influence on student performance, while passive methods like note checking showed minimal impact. Assignments and viva voce were perceived as valuable for developing analytical reasoning and verbal articulation, although they sometimes generated stress. Poster presentations were effective in enhancing communication and creativity, but received mixed responses regarding mathematical depth. These results align with educational psychology frameworks, suggesting that active engagement reduces cognitive load and enhances intrinsic motivation. The study concludes that integrating diverse and interactive assessments fosters deeper conceptual understanding, problem-solving ability, and sustained engagement among engineering students. Implications for faculty, curriculum developers, policy makers, and educational technologists are discussed, particularly in terms of redesigning assessment frameworks and supporting professional development for educators.